34.5k views
1 vote
For the equation

ax + c = bx + d where a ≠ b and c ≠ d, what is x expressed in terms of a,b,c and d?

1 Answer

4 votes


x=(d-c)/(a-b)

Explanation:

Step 1 - Given data:

ax + c = bx + d,

where a ≠ b and c ≠ d

Step 2 - To find:

x expressed in terms of a, b, c and d.

Step 3 - Solution:

The equation is ax + c = bx + d

⇒ ax – bx + c = d

Arrange x variables on one side, then the equation becomes

⇒ ax – bx = d – c

Take x term as a common factor, then the value becomes

⇒ (a – b)x = d – c

x expressed in terms of a, b, c and d is


x=(d-c)/(a-b)

User Jeffin
by
5.8k points